Corporate Gita: lessons for management, administration and leadership - Sharma, Subhash (1999)
This paper expounds the model of a `sacro-civic' society, drawing upon psycho-spiritual insights of the Gita. Four major management themes of common interest in the East and the West have been selected. Then the relevant verses of the Gita have been used to elaborate on their respective deeper imports. These four broad themes have later again been decomposed into 20 specific subthemes, and verses connected with each of them are presented. The author offers simple rhymed English translations of these verses using some of the well-known renderings by earlier masters of the Gita. The reader is invited to reflect upon and assimilate the spirit of these verses for application in the field of daily management practice and in the wider arena of social reconstruction. - Reproduced
Keywords: Public administration - India; Leadership - India; Gita; Management - India; Management